Optimization of Social Media and Product Photography as Promotional Media for Geopark Weaving Group in Supporting Air Batu Tourism Village, Renah Pembarap District, Merangin Regency, Jambi Province - Nurhayani; Tan, Syamsurijal; Rahmadi, Selamet; Rosmeli; Ekasari, Novita (Jurnal Karya Abdi Masyarakat, 2026)
The Geopark Weaving Group is one of the business groups located in Air Batu Village. This weaving group supports the development of the tourist village by continuously developing and improving its products. However, the group faces several challenges, including the lack of social media accounts and limited skills in creating attractive product photography. The purpose of this community service activity was to improve marketing by focusing on the application of digital technology through social media and product photography. The implementation of these technologies is expected to enhance product promotion, expand the market in the digital era, and support the development of the tourist village through continuous product innovation. Following the community service activity, the weaving group successfully established social media accounts and acquired the ability to create attractive product photographs, although they are still in the learning stage. The weaving business group expressed great appreciation for the assistance provided by the KKNT students in supporting the development of Air Batu Tourism Village. In addition to implementing the community service program, the students also participated in various activities conducted by the village community, including teaching at schools, supporting community health services (Posyandu), participating in arts activities, and other community programs. The methods used in this community service activity were lectures, discussions, and training. It is expected that the partners will cooperate actively and participate throughout the implementation of the program so that the established objectives can be achieved.